Ways of resolving semantic differences in translating English legal terms (based on EU civil law documents) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article investigates the peculiarities of English translation of legal terms into Ukrainian based on semantic changes taking place here. It has been determined that the national- legal component of the content is peculiar of legal terminology both in English and Ukrainian. The criteria of reproducing semantics of civil terms have been described.
Keywords: civil law terminology; metaphor; polysemy; homonymy